PENGARUH TEKANAN AKUNTABILITAS DAN SELF-EFFICACY TERHADAP KINERJA AUDITOR DENGAN MENGGUNAKAN EFFORT SEBAGAI MEDIASI - Andrew Joscha Sinaga (CALYPTRA, 2019)
Abstract - Audit judgment is a consideration of the evidence and documentation that influences the decisions made by the auditor so that the necessary corporate honesty in presenting the financial statements and the auditor in conducting auditing. There are several factors that affect audit judgment among other pressures of accountability, self-efficacy, and the effort of the auditor. This research aims to examine the influence between the pressures of accountability and self-efficacy against the effort and audit the auditor's judgement in Surabaya. The sample used totaled 200 persons of public accountant in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of structural equation models. The results of this analysis indicate that the pressures of accountability, and self-efficacy were found positive and significant effect against the effort and audit judgement. In addition, the study also showed that the effort could increase the audit judgement. Keywords: Accountability; Self-efficacy; Effort; Audit Judgment.